Contrast-Enhanced Color Doppler Ultrasonography for Preoperative Evaluation of Sentinel Lymph Node in Breast Cancer Patients - Dellaportas, Dionysios (Breast Care (Basel), 2015)
BACKGROUND: Sentinel lymph node (SLN) biopsy is the standard of care for breast cancer patients with non-palpable axillary lymph nodes. We evaluated the usefulness of contrast-enhanced ultrasonography in preoperative detection of malignant SLNs. METHODS: 50 patients with breast cancer (median age: 60 years) underwent a color power Doppler ultrasonography with intravenous contrast (Sonovue®) preoperatively, and findings suggestive of metastatic disease to the SLN were documented. The final histopathological report and the radiological preoperative record were compared. Finally, the sensitivity, specificity and diagnostic accuracy of this evolving diagnostic modality were calculated. RESULTS: Contrast-enhanced ultrasound scan identified a negative SLN in the axilla of 27 patients and final histopathology was negative for 30 cases in total, so negative predictive value was calculated as 90% and positive predictive value was 75%. Overall sensitivity was 83.33% and specificity was 84.38%. Moreover, the ability of contrast-enhanced ultrasound to differentiate between SLN status was only statistically significantly correlated with the actual final histopathological report (p < 0.001), while successful ultrasound prediction was not correlated with any factor. CONCLUSIONS: SLN status can be evaluated preoperatively using contrast-enhanced color Doppler ultrasonography with high accuracy.